ESPECIFICAÇÃO DE UM SISTEMA MULTIAGENTE DE RECOMENDAÇÃO DE AÇÕES EM CASO DE FALHAS DE SISTEMAS DE AUTOMAÇÃO E CONTROLE - Quintão, Heider Cristian Moura (2008)
When equipment failure occur in complex industrial plants, the automation and control system generates a great amount of alarms that can confuse the operators and lead them to take wrong decisions - the time for decision taking is very short and the amount of generated information is higher, being impossible for the operator read all of them before taking the correct decision. The new industrial systems have presented functionalities that try to minimize this deficiency presenting some support to the user, but still in an inefficient form. This work presents a proposal of an Alarm Management System based on Action Recommendation - SIGARA, a knowledge-based tool which aims supporting users of industrial control systems, when abnormal events occur. SIGARA is an action recommender multi-agent system, shaped on the basis of the described tasks and phases of the ONTORMAS ontology and MAAEM methodology. Beyond searching the solution of a problem of the real world in the industries, the proposed SIGARA presents some additional features not present on existing systems, as the application of information filtering techniques in different processing phases, and also the use of MAAEM and ONTORMAS in this new domain.